Holiday Economics: Perspectives and Experiences from Hospitality Professionals - Era, Joy Sheelah Baraero; Eje, Mary Shan Cai; Hernaez, Jhamela Kate; Gonzales, Shaira Karylle (Centre For Tourism Planning and Development, 2025)
This research examined the perspectives and experiences of hospitality professionals on the resurgence of the Philippine Holiday Economics Law, first enacted in 2007, discontinued in 2010 under the Aquino administration, and revived in 2022 during the Marcos administration. The policy strategically shifts holidays to create long weekends and boost domestic tourism as part of its recovery program following the COVID-19 pandemic. Based on grounded theory and lived experience theoretical perspectives, this study employed a qualitative research design through semi-structured interviews with 15 hospitality professionals working in six restaurants, five cafes, and four hotels in Bonifacio Global City, Taguig, Philippines. The results revealed that the concept of holiday economics is ambiguous to the participants, yet they have experienced its impact on operations and the workforce. This pioneering study provides actionable insights for stakeholders, facilitating more effective policy implementation. It contributes to understanding how a specific law or tourism-related policy on holiday adjustments is perceived and how it impacts the operations and workforce of hospitality professionals in a particular setting, which could serve as the foundation for similar studies in diverse contexts.